2011
DOI: 10.1021/ja1088748
|View full text |Cite
|
Sign up to set email alerts
|

Evidence That Epoxide-Opening Cascades Promoted by Water Are Stepwise and Become Faster and More Selective After the First Cyclization

Abstract: A detailed kinetic study of the endo-selective epoxide-opening cascade reaction of a diepoxy alcohol in neutral water was undertaken using 1H NMR spectroscopy. The observation of monoepoxide intermediates resulting from initial endo and exo cyclization indicated that the cascade proceeds via a stepwise mechanism rather than through a concerted one. Independent synthesis and cyclization of these monoepoxide intermediates demonstrated that they are chemically and kinetically competent intermediates in the cascad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 49 publications
2
21
0
Order By: Relevance
“…9,10 In particular, the observed stereoselectivity for inversion of configuration at the anomeric carbon may be attributed to either of two possible reaction mechanisms (Figure 2). An S N 2 reaction manifold (pathway A) would require sufficient hydrogen-bonding activation of the epoxide electrophile to induce nucleophilic substitution by the sidechain hydroxyl group without formation of a discrete oxocarbenium intermediate, which might lead to reduced stereoselectivity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…9,10 In particular, the observed stereoselectivity for inversion of configuration at the anomeric carbon may be attributed to either of two possible reaction mechanisms (Figure 2). An S N 2 reaction manifold (pathway A) would require sufficient hydrogen-bonding activation of the epoxide electrophile to induce nucleophilic substitution by the sidechain hydroxyl group without formation of a discrete oxocarbenium intermediate, which might lead to reduced stereoselectivity.…”
Section: Resultsmentioning
confidence: 99%
“…Jamison and coworkers have reported second-order catalysis by water in their landmark studies of regioselective epoxide-opening cascades to form ladder polyethers. 9 Williams and coworkers have provided computational support for hydrogen-bonding catalysis at the distal epoxide in their intriguing work on spirodiepoxide-opening reactions. 10 To date, however, the role of hydrogen-bonding catalysis in epoxide-opening spirocyclizations of glycal epoxides, and the critical and distinctive impact upon stereoselectivity in this reaction, has not been studied in detail.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 The presence of the oxygen in the heterocyclic ring was vital for the desired selectivity. It has also been suggested that enzymes may catalyze the formation of an initial THP ring, and that this THP then “templates” the cascade favoring an all endo ring closure sequence.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to uncovering the specific details about epoxy alcohol cyclization reactions, these mechanistic studies are relevant to the biosynthetic proposal (18) for the formation of the ladder polyether natural products. The very slow reaction rates observed for 1a and even slower rates for cascade reactions of multiple epoxides, such as 4 and 6 (12,24), are problematic for a biosynthetic proposal involving consecutive or concurrent epoxy alcohol cyclizations promoted by neutral water. The data presented above suggest rate constants for endo cyclizations to be on the order of 10 −5 ·s −1 at 300 K, which translates to a half-life of 16.6 h. These rates seem unlikely under physiological conditions where metabolism or extrusion of intermediates during a cascade reaction would compete.…”
Section: Implications For the Biogenisis Of The Ladder Polyether Naturalmentioning
confidence: 99%